2006
DOI: 10.1172/jci28422
|View full text |Cite
|
Sign up to set email alerts
|

Injury-induced innate immune response in human skin mediated by transactivation of the epidermal growth factor receptor

Abstract: We found that sterile wounding of human skin induced epidermal expression of the antimicrobial (poly)peptides human β-defensin-3, neutrophil gelatinase-associated lipocalin, and secretory leukocyte protease inhibitor through activation of the epidermal growth factor receptor. After skin wounding, the receptor was activated by heparin-binding epidermal growth factor that was released by a metalloprotease-dependent mechanism. Activation of the epidermal growth factor receptor generated antimicrobial concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
129
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(138 citation statements)
references
References 43 publications
(52 reference statements)
7
129
0
2
Order By: Relevance
“…These studies on the increase of human ␤-defensin 2 expression in wound healing are further supported by studies made by Sørensen et al (32,33), who found that the growth factors important in wound healing, insulinlike growth factor I and TGF-␣, induce the expression of several antimicrobial peptides/polypeptides in human keratinocytes such as human cationic antimicrobial protein hCAP-18/LL-37, human ␤-defensin 3, neutrophil-gelatinase-associated lipocalin, and secretory leukocyte protease inhibitor, defining a host defense role for growth factors in wound healing. Thus, in the case of skin injury, both extracellular matrix components and growth factors may contribute to the production of an array of protective antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 56%
“…These studies on the increase of human ␤-defensin 2 expression in wound healing are further supported by studies made by Sørensen et al (32,33), who found that the growth factors important in wound healing, insulinlike growth factor I and TGF-␣, induce the expression of several antimicrobial peptides/polypeptides in human keratinocytes such as human cationic antimicrobial protein hCAP-18/LL-37, human ␤-defensin 3, neutrophil-gelatinase-associated lipocalin, and secretory leukocyte protease inhibitor, defining a host defense role for growth factors in wound healing. Thus, in the case of skin injury, both extracellular matrix components and growth factors may contribute to the production of an array of protective antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 56%
“…The growth factor TGF␣ has been shown to induce AMP expression in keratinocytes (45), whereas HBEGF was shown to stimulate EGFR, leading to the induction of antimicrobial peptides (46). When coupled with our results of synergy between dsRNA and LL-37 leading to growth factor production, we can envision a positive feedback loop.…”
Section: Discussionmentioning
confidence: 54%
“…Il en est certainement de même dans la peau des mammifères où une piqûre stérile provoque l'induction d'AMP [41].…”
Section: Revuesunclassified